2000
DOI: 10.1002/1097-0126(200010)49:10<1177::aid-pi437>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Solid state 13C and in situ 1H NMR study on the effect of melamine on the thermal degradation of a flexible polyurethane foam

Abstract: The aim of this investigation is to ascertain whether the mode of action of melamine in exible polyurethane (PU) involves condensed phase chemistry in terms of promoting char formation. A combination of in situ 1 H NMR analysis, solid state 13 C NMR characterization of chars prepared ex situ, and normal TGA and DSC has been employed. Solid state 13 C NMR indicates that there is no major discernible difference in the structure of the dichloromethane-insoluble chars prepared with and without melamine, the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Bastin et al suggested that the synergistic effect is that the TDCPP generates phosphoric acid, which promotes the conversion of melamine into thermally stable network structures such as melam, melem, and melone [24]. Dick et al used 1 H NMR spectroscopy to find that the melamine additive acts in the condensed phase by promoting the formation of a rigid char at temperatures above 400ºC [25]. Melamine is also believed to act as a heat sink, and the nitrogen content of melamine may partly end up as nitrogen gas, providing a heat sink and diluent in the gas phase [26].…”
Section: Pyrellmentioning
confidence: 99%
“…Bastin et al suggested that the synergistic effect is that the TDCPP generates phosphoric acid, which promotes the conversion of melamine into thermally stable network structures such as melam, melem, and melone [24]. Dick et al used 1 H NMR spectroscopy to find that the melamine additive acts in the condensed phase by promoting the formation of a rigid char at temperatures above 400ºC [25]. Melamine is also believed to act as a heat sink, and the nitrogen content of melamine may partly end up as nitrogen gas, providing a heat sink and diluent in the gas phase [26].…”
Section: Pyrellmentioning
confidence: 99%
“…Owing to emission of toxic and dense smoke, the use of halogen flame retardants is limited. As a result, halogen‐free flame retardants such as ammonium polyphosphate,2–4 expandable graphite,5–10 and melamine11–15 are used in the flexible polyurethane foams. In fact, inorganic hydroxide fillers have replaced halogen flame retardants in many plastic applications due to benefits such as low cost as well as minimal corrosiveness relative to the antimony‐halogen systems and phosphorus‐containing fire retardants.…”
Section: Introductionmentioning
confidence: 99%
“…ermogravimetric analysis (TGA) is widely used to evaluate the thermal stability of polyurethane [33][34][35][36]. TG and DTG curves of SPUF composites with different flame retardants under nitrogen atmosphere are presented in Figure 1.…”
Section: Ermal Propertiesmentioning
confidence: 99%